A percepção dos professores sobre adolescentes com altas habilidades/superdotação na escola - Annunciato Neto, Rafael [UNIFESP] (2019)
Adolescents with high skills/giftedness in school may be invisible in the eyes of the school and teachers, considering the insignificant levels of attendance, since there are less than 0,05% of students identified in the 2018 school census. They are contemplated in Federal Decree n° 7.611, dated November 17, 2011, which provides for Specialized Educational Assistance (AEE); however, it can be seen from the indicators that they remain outside the school radar. Objective: To identify how the teacher and the school perceive the high skills / giftedness of adolescents with high social vulnerability in school. Method: Systematic review of the literature that used the descriptors "Child, gifed" and "Academic Success" in the databases: IBCT; Google Academic; MedLine; Cochrane; PubMed; Lilacs; Pilots; (Capes); and SciELO. As criterion of inclusion will be determined: 1) article, thesis, book; 2) qualitative studies; 3) adolescents; 4) perception of teachers and coordinators; and 5) work involving the schooling process. And as criteria of exclusion: documents that do not have a single and direct relationship with students with high skills / giftedness; 2) completion of graduation courses, specialization courses and lato-sensu. Qualitative studies, articles, theses, dissertations, annals of congresses, book chapter, book in Portuguese, Spanish and English were considered. Results: 903 papers were identified, of these 355 duplicates, totaling 548 papers. The identified works were evaluated, and six papers were selected to compose the systematic analysis. Discussion: teachers' statements were classified into six categories: myths and prejudices; identification / evaluation; invisibility, teacher training and socio-emotional vulnerability. The analysis was theoretically grounded, involving issues of legislation, theories about intelligence and identification processes. The health dimension was addressed as a fundamental component to avoid disorders resulting from socioemotional vulnerability. Final considerations: when analyzing all the evidence, it can be understood that there is no single cause, but several factors added together produce invisibility in the school system. Evidence shows that there is no educational policy to develop students with higher academic performance. New paths need to be built to reverse this situation once the legislation itself is ambiguous, where the school is not obliged to develop its students, and so little guarantee health care. Urges the need to create lasting public policies that can correct distortions in legislation and guarantee student’s full education and health care.